ESTUDO SOBRE A VIABILIDADE DE PRODUÇÃO DO ETANOL DE PRIMEIRA GERAÇÃO E ETANOL DE SEGUNDA GERAÇÃO - KELLY CRISTINA COSTA CAMARGO (2023)
First-generation ethanol (alcohol or ethyl alcohol) is an energy source of renewable raw material widely used by the world's population as fuel and in other types of products. In addition to producing ethanol from known processes, there is the possibility of producing second-generation ethanol from residues and components that are not used in the production process of first-generation ethanol. Brazil is the second largest producer of ethyl alcohol and the largest producer of sugarcane. Ethyl alcohol uses sugarcane and bioethanol uses available biomass, such as sugarcane bagasse, showing great potential for the country in the manufacture of bioethanol. The bioethanol manufacturing process uses lignocellulosic biomass, and the production steps are made by manufacturing ethyl alcohol, adding the processes of pre-treatment, hydrolysis and fermentation of pentoses. In the hydrolysis step, the glucose liquor is generated, which is sent to the broth concentration process, where the water in the broth is evaporated and the broth is cooled in two heat exchangers. This work aims to show, through a bibliographic review, the production processes of first and second generation ethanol, and through comparative analyses, point out the main differences and what are the advantages of second generation ethanol, when compared to first generation ethanol. Among the advantages of second-generation ethanol, the increase in ethanol production stands out, without increasing the area planted with sugarcane, increasing general efficiency, technological development and worker income, and reducing environmental impacts. . A negative point is still the higher cost of production, compared to first-generation ethanol, which prevents large-scale commercialization. Keywords: Ethanol, Second generation ethanol, Comparison, Feasibility.